Microblog opinion evolution model - Yu, Jiaqing (2016)
Retweeting is an important behavior on Twitter, indicating the behavior that users repost microblogs of their friends. While much work has been conducted for mining textual content that users generate or analyzing the social network structure, few publications systematically study the underlying mechanism of the retweeting behaviors. In this project, a new opinion evolution model is put forward. Based on several important observations, this model is developed to predict users’ view dissemination in a particular group. Several comparison Experiments have been done to show that the sensitivity as well as activity has a role to promote the dissemination of information.